Phytochemicals and antioxidant activities of conventionally propagated nodal segment and in vitro-induced callus of Bougainvillea glabra Choisy using different solvents - Nasrat, Mohammad Nasim; Sakimin, Siti Zaharah; Hakiman, Mansor (MDPI, 2022)
Bougainvillea, popularly known as ‘Bunga kertas’ in Malaysia, is thoroughly explored for nutritional and medicinal purposes. Bougainvillea has been shown to possess alkaloids and flavonoids which are widely used in folk medicine to treat different illnesses such as inflammatory, diarrheal, ulcer, and diabetic. Despite its major conventional therapeutic importance, only limited attempts have been made to investigate this species’ chemical and pharmacological properties in relation to its medicinal uses. Therefore, this study was conducted to determine the effect of in vitro-induced callus under different light conditions and plant growth regulators on phytochemical and antioxidant activities using different extraction solvents. Based on the results, the maximum days (17.67) to callus initiation were recorded when nodal was cultured on woody plant medium (WPM) supplemented with 7.5 µM 2,4-D + 0.5 µM BAP under light condition. On the contrary, the minimum days (7) to callus initiation were obtained when nodal was treated with 2.5 and 5 µM 2,4-D + 1 and 1.5 µM BAP under dark conditions. However, higher fresh and dry weight of callus was obtained when nodal was cultured on woody plant medium fortified with 7.5 µM 2,4-D + 1.5 µM BAP under dark and light conditions. In the analysis of the phenolics content and antioxidant activities, aqueous extract of conventionally propagated nodal part exhibited the highest phenolic content and antioxidant activities. However, the highest iron (II) chelating activity was produced from the aqueous extract of the calli induced under a dark condition. Hence, it can be concluded that the callus culture of Bougainvillea produced plant secondary metabolites and antioxidant activities comparable to the mother plants.